BALANCING INNOVATION AND INTEGRITY: STUDENTS' PRACTICES IN USING AI FOR ACADEMIC AND CREATIVE TASKS - Atiqa Nur Latifa Hanum; Dewi Ismu Purwaningsih (JURNAL EDUSCIENCE, 2026)
Purpose- This study aims to describe students' practices in using AI as a creative partner in coursework, analyze strategies that support creativity and critical thinking, and explore ethical challenges, including plagiarism.Methodology- This is a qualitative phenomenological approach; data were collected through non-participant observations and in-depth interviews with students and librarians from five universities in Pontianak. The study also utilized secondary sources and NVivo software to manage, code, and visualize data.Finding- The findings reveal that students use AI tools such as ChatGPT, Google Bard, and other AI-based platforms to complete assignments, search for references, and create multimedia content. AI was reported to increase efficiency, support creative exploration, and personalize learning experiences. However, risks such as overdependence, plagiarism, and reduced independent thinking were also evident. Educators emphasized the need for digital and AI literacy training to ensure ethical and responsible use of AI.Contribution- AI provides significant benefits in supporting academic and creative tasks but simultaneously poses ethical and pedagogical challenges. The study recommends developing institutional policies, training programs, and guidelines that balance innovation with academic integrity.